G156(P) Moving from child to adult health care: development of benchmarks for transition. (27th April 2015) - Aldiss, S; Rose, L; Cass, H; Ellis, J; Gibson, F
Abstract : Background: Transition from child to adult health care for young people with long-term conditions is currently a 'hot topic' within the NHS. In spite of the growing evidence base, the implementation of transitional care remains a challenge. Lack of 'being prepared' was a main finding from young people and parents reported by the Care Quality Commission (CQC) in 2014. Here only 54% of young people described preparation for transition that had enabled them to be involved in the process and 80% of pre-transition case notes reviewed had no transition plans for health. The CQC recommend that existing good practice guides be followed to ensure young people are properly supported through transition. Benchmarks offer a guide/standards that services can measure themselves against to see how they are doing, where they could improve and can facilitate the sharing of best practice. Aims: To describe the development of a clinical practice-benchmark tool for transition. Method: This qualitative study involved focus groups, workshops and interviews. Data were collected from young people with long-term health conditions, their parents, professionals and experts leading on transition within the UK. Transcripts were analysed using qualitative content analysis. The focus was to develop an increased understanding of transition, from multiple perspectives, and to describe what strategies and resources might be required to facilitate transition with the aim of developing a benchmark tool. Results: For young people and their parents/carers to experience timely and effective transition 8 factors and their associated indicators of best practice statements have been developed from the data: young people and parents led on selecting the factors and practice statements. Communication, co-ordination, gradual transition and support to manage their health condition as an adult were paramount for them. The tool was distributed to a range of professionals across the UK for comment and subsequently refined to produce the current benchmarks. Conclusion: The need for change, in order to best meet the needs of young people, and parents during transition is very evident. This paper will describe the development of benchmarks for transition, which indicate young people and parents' needs and preferences regarding transition to adult care.